Surface modification of nanofiltration membrane using polyoxometalates for improved separation and antifouling performance - Lu, Qi (Water science and technology : a journal of the International Association on Water Pollution Research, 2024)
In this study, polyoxometalates (POMs) as a core-modifying material was used to fabricate the nanofiltration (NF) membrane on the polyvinylidene fluoride (PVDF) microfiltration membrane substrate via a novel interfacial polymerization (IP) method. The formation mechanism of the POMs-modified composite membrane was proposed. The separation and antifouling properties were further investigated. After cross-linking with POMs through the new IP reaction, the modified composite membrane showed improved hydrophilicity, water flux, and salt rejection. In the humic acid fouling experiment, the POMs-modified membrane exhibited the best antifouling performance, with a flux recovery rate of up to 91.3%. Electrochemical impedance spectroscopy was further used to investigate the antifouling performance of the membranes. Nyquist and Bode plots of the POMs-modified membranes showed no significant change before and after fouling compared to the PVDF membrane substrate, indicating reduced fouling attachment on the modified membrane, which was consistent with the fouling index and flux variation observed during the fouling experiment. Our findings provide a simple and valuable route for fabricating POMs-functionalized NF membranes with desirable separation and antifouling performance